Solitary Troubles - Reinert, Alexander A. (2018)
Solitary confinement is one of the most severe forms of punishment that can be inflicted on human beings. In recent years, the use of extreme isolation in our prisons and jails has been questioned by correctional officials, medical experts, and reform advocates alike. Yet for nearly the entirety of American history, judicial regulation of the practice has been extremely limited. This Article explains why judges hesitate to question the use of solitary confinement, while also providing a path forward for greater scrutiny of the practice